Efektivitas Penggunaan Ventilasi Mekanis Non Invasif Pada Pasien Penyakit Paru Obstruktif Kronik Eksaserbasi Dengan Ancaman Gagal Napas: Evidence-Based Case Report - Fadhlurrahman; Adityo Wibowo (CV. Jasa Sukses Abadi, 2022)
Chronic obstructive pulmonary disease (COPD) is a chronic disease characterized by impaired airflow within the respiratory tract and is an increasing global health problem, characterized by airway obstructiveness, chronic obstructive bronchiolitis and emphysema. The disease is caused by prolonged exposure to cigarette smoke as well as air pollution. Symptom and risk management also include pharmacological and non-pharmacological treatment. COPD patients could experience shortness of breath with or without the threat of respiratory failure. Non-invasive ventilation is a non-pharmacological intervention used to treat severe COPD shortness of breath and to help the respiratory muscles work properly. This study aimed to see how non-invasive mechanical ventilation worked as a treatment for respiratory failure in patients with chronic obstructive pulmonary disease. Articles were searched in several databases, including PubMed/MEDLINE, ScienceDirect, Nature Journal, and Google Cendikia, using keywords related to clinical scenarios published between 2016 and 2022. The articles discovered were then subjected to a critical analysis using the Center of Evidence worksheet. Oxford-based Medicine Conclusion: According to the findings of the article analysis, patients with chronic obstructive pulmonary disease (COPD) treated with noninvasive mechanical ventilation had a lower risk of mortality and intubation.